The impact of Giloy (Tinospora cordifolia) and Amla (Emblica officinalis) Herbal Feed Additives on the Morphometric Traits of Magra Lambs Raised under the Extensive Rearing System in Western Rajasthan, India - , Abhishek Joshi; , Nirmala Saini; , Vishal Yadav; , Rajpal Singh Udawat; , Rajesh Mohta; , S. C. Goswami (Archives of Current Research International, 2024)
The objective of this research was to explore the utilization of herbal feed supplements, precisely amla (Emblica officinalis) and giloy (Tinospora cordifolia), affects the morphometry of Magra lambs under an extensive management system. The study involved 28 Magra lambs aged 3-4 months, placed within an extensive system. These lambs were randomly allocated into 04 experimental groups, each consisting of 7 lambs, using a randomized block design (RBD). In an extensive management system, Amla (Emblica officinalis) whole fruit powder and Giloy (Tinospora cordifolia) stem powder, herbal feed additives, were provided at a dosage of 1.5 gram per kilogram body weight with concentrate for T1 and T2 groups, respectively. This supplementation was excluded for the control group, and a different approach was followed for T3. T3 group received a combined supplement of Amla whole fruit powder and Giloy stem powder at a concentration of 0.75 gram per kilogram body weight, administered alongside concentrate as oral/feed. By the conclusion of the experiment, notable alterations were observed in measurements such as abdominal girth, chest/heart girth, body height, and body length; however, these changes remained within the standard range of morphometric traits. At the conclusion of the experiment, it seems that integrating 1.5 gram per kilogram body weight of giloy stem powder and amla powder can be considered a viable component of the strategy, as it proves effective in enhancing morphometric traits in lambs within the extensive management system of the arid zone of Rajasthan.